Television in Post-Reform China: Serial Dramas, Confucian Leadership and the Global Television Market - Zhu, Ying (Routledge, 2008)
This book explores the political, economic, and cultural forces, locally and globally that have shaped the evolution of Chinese primetime television dramas, and the way that these dramas in turn have actively engaged in the major intellectual and policy debates concerning the path, steps, and speed of China’s economic and political modernization during the post-Deng Xiaoping era. It intertwines the evolution of Chinese television drama particularly with the ascendance of the Chinese New Left that favors a recentralization of state authority and an alternative path towards China’s modernization and China’s current administration’s call for building a "harmonious society." Two types of serial drama are highlighted in this regard, the politically provocative dynasty drama and the culturally ambiguous domestic drama. The book also provides cross-cultural comparisons that parallel the textual and institutional strategies of transnational Chinese language TV dramas with dramas from the three leading centers of transnational television production, the US, Brazil and Mexico in Latin America, and the Korean-led East Asia region. The comparison reveals creative connections while it also explores how the emergence of a Chinese cultural-linguistic market, together with other cultural-linguistic markets, complicates the power dynamics of global cultural flows.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Prime Time Soap Operas on Indian Television - Munshi, Shoma (Routledge India, 2020)
This book examines the phenomenon of prime time soap operas on Indian television. An anthropological insight into social issues and practices of contemporary India through the television, this volume analyzes the production of soaps within India’s cultural fabric. It deconstructs themes and issues surrounding the "everyday" and the "middle class" through the fiction of the "popular". In its second edition, this still remains the only book to examine prime time soap operas on Indian television. Without in any way changing the central arguments of the first edition, it adds an essential introductory chapter tracking the tectonic shifts in the Indian "mediascape" over the past decade – including how the explosion of regional language channels and an era of multiple screens have changed soap viewing forever. Meticulously researched and persuasively argued, the book traces how prime time soaps in India still grab the maximum eyeballs and remain the biggest earners for TV channels. The book will be of interest to students of anthropology and sociology, media and cultural studies, visual culture studies, gender and family studies, and also Asian studies in general. It is also an important resource for media producers, both in content production and television channels, as well as for the general reader.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Koweït (lieu de production du savoir); _Nettoyé

Tears, Talk, and Play: A Window to Gender and Sexuality on Tamil Television - Vangal, Uma (Channeling Cultures: Television Studies from India, 2014)
Tamil television lends itself to some interesting initiatives in gender empowerment through its programming in 3 categories – fiction, reality, and talent shows. This chapter provides a glimpse into television programmes on leading Tamil channels over the last decade (2000–10) from a gender perspective. Focusing particularly on women and transgender characters/hosts, emotional and psychological quotients of the shows and their audiences, moments of dramatic intensity, the chapter demonstrates how the vernacular televisual representations were quite different from the stereotypical portrayals of the mainstream ‘national’ television, even though the programmes were produced, televised, and received within the broader patriarchal framework of Tamil cultural and political contexts. The chapter, as a whole, intends to look at the production, representation and identification of Tamil television soaps and reality shows as vehicle for spotlighting gender issues and alternative sexualities in the public domain.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

The Saffron Hues of Gender and Agency on Indian Television - Chakrabarti, Santanu (Channeling Cultures: Television Studies from India, 2014)
This chapter explores the contradiction between two sets of responses to the so-called K-serials, earlier, largely condemnatory ones, and more recent, largely laudatory ones. The chapter aims to understand this contradiction and resolve it. It does so by showing how K-serials were a definitive break at that specific point in time from the ones that had immediately preceded them, especially in bringing to the fore the bahu (daughter-in-law) of Hindu urban extended families. It traces the complex place of gender in the discourse of the Hindu right and explores the strong debt that the K-serials owe to the ideological constructions of the woman and the family by Hindu nationalism. It argues therefore that the consequences of celebrating agency and empowerment in a right wing milieu-as some recent scholarship has done-ends up advocating for a limited and exclusionary form of female agency.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

Television, Narrative Identity, and Social Imaginaries: Hermeneutic Approach - Asthana, Sanjay (Channeling Cultures: Television Studies from India, 2014)
The chapter argues that Paul Ricouer’s hermeneutics offers a way forward in examining not only the ideological and narrative structures of television, but also particular modalities through which viewers appropriate and interpret televisual texts. To this end, the chapter shall sketch an analytic framework by bringing together Ricoeur’s hermeneutic philosophy, particularly his concepts of narrative identity and temporality, and the notion of social imaginaries developed by postcolonial theory in a productive dialogue. Ricoeur’s hermeneutics presents an understanding of the human subject in terms of an embodied subjectivity that takes us beyond singular conceptions of identity, whether in terms of the abstract Cartesian subject, or various other discourse-centred theorizations of subject. The chapter demonstrates that the notion of embodied subjectivity and social imaginaries enable a better grasp in examining the articulations of class, caste, gender, and religious identities on Indian television.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Gender, Ideology and Latin American Children's Animated Television - Gonzalez-Rodriguez, Milton Fernando (Children, Youth, and International Television, 2022)
Animation allows for the creation of mediatic spaces that strengthen prevailing ideologies of masculinity and femininity. Manhood seems to operate as a key point of reference in the creation of televised animation across Latin America, especially by elevating certain heroic cultural narratives. Through a review of 21 television series, produced between 2008 and 2018, this chapter examines the portrayals of femininity and masculinity in some of the most widely broadcast animated series from the region. As a norm, Latin American illustrators adhere to the tradition of depicting female figures as secondary characters, as leading characters with a certain degree of autonomy, or as subaltern, considerate, and supportive figures. By contrast, male figures are portrayed as strong, daring, independent, and primary characters, often destined to lead their families and communities, and save their weaker friends that are typically female characters.
Num Pages: 11
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Argentine (corpus analysé); Belgique (lieu de production du savoir); Brésil (corpus analysé); Chili (corpus analysé); Colombie (corpus analysé); Mexique (corpus analysé); Pérou (corpus analysé); _Nettoyé

The Evolution of Black Women in Television: Mammies, Matriarchs and Mistresses - Cheers, Imani M. (Routledge, 2017)
This book seeks to interrogate the representation of Black women in television. Cheers explores how the increase of Black women in media ownership and creative executive roles (producers, showrunners, directors and writers) in the last 30 years affected the fundamental cultural shift in Black women’s representation on television, which in turn parallels the political, social, economic and cultural advancements of Black women in America from 1950 to 2016. She also examines Black women as a diverse television audience, discussing how they interact and respond to the constantly evolving television representation of their image and likeness, looking specifically at how social media is used as a tool of audience engagement.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Television and Dating in Contemporary China: Identities, Love and Intimacy - Yang, Chao (Palgrave Macmillan Singapore, 2017)
"This book considers the changing nature of intimacy in contemporary China, providing a unique case study of romantic subjectivities in young people in the world's fastest growing economy. Since the implementation of reform in 1978, the economic and socio-cultural environment of modern China has experienced a dramatic transformation under the influence of urbanization and globalization, facilitating more individualized identity among Chinese youth. This book bridges the gap between an emergent emphasis on individualisation and the country's traditional norms and values. It focuses on young people's understandings of various forms of relationships such as cohabitation, extramarital relationships and multiple relationships, suggesting a challenge to traditional familial values and an increasingly diversified understanding of the concepts of love and romance. By examining the formation of relationships among 21st century Chinese youth, notably through the lens of popular Chinese TV dating programs, this book considers how dating and relationships mirror China's changing societal structure and examines social and cultural transformations in Chinese society."
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Bridal Anxieties: Politics of Gender, Neoconservatism and Daytime TV in Turkey - Sayan-Cengiz, Feyda (Female Agencies and Subjectivities in Film and Television, 2020)
This chapter analyzes the reflections of Turkey’s neoconservative and neoliberal politics of gender on daytime television. The focus is on Bridal House, a popular daytime TV show in Turkey which interpellates women as domestic subjects competing with other women to prove their domestic abilities, particularly the ability to navigate the etiquette of domestic consumption. Hierarchies are instigated among women through symbolic battles on “tasteful” consumption, and the marital household surfaces as a space of constant regulation where women strive to be ideal housewives. By analyzing Bridal House through a Bourdieusian framework, this chapter traces the representations of the “ideal female subject” along neoconservative and neoliberal lines, and demonstrates the ways in which symbolic violences are enacted on women in contemporary Turkey’s daytime TV culture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Producing Domestic Abuse in Pakistani Television: Between Commerce, Ratings and Social Responsibility - Cheema, Munira (Television for Women, 2016)
Before the liberalisation of television in 2000, Pakistan had one terrestrial channel.The Pakistan Television Corporation (commonly known as PTV) had been the statebroadcaster since 1964 and thus PTV content reflected the policies of differentgovernments. Liberal governments relaxed control over gender on screen – womencould be seen without dupatta – while religiously inclined governments brought intheir own agendas with restrictions on appearance of women, such as the dupattapolicy (see, for example, Ali, 1986; Suleman, 1990; Kothari, 2005; Nasir, 2012).1 In2002, the Independent Media Corporation launched its channel Geo News fromPakistan, followed by other networks, marking the formal launch of the policy ofliberalisation of media on television. Presently, five media groups have control of thePakistani media industry, including electronic and print media. These are Inde-pendent Media Corporation, Pakistan Herald Publications, ARY Group, WaqtGroup and Lakson Group (see for example Proffitt and Rasul, 2013). The broad-casting industry in Pakistan follows an advertiser-driven model that is run through asystem of ratings. At the time of the fieldwork reported here (October-April 2011),Media Logic and Gallup were the two operators that determined the popular tastesof consumers through ratings.2
Num Pages: 20
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 5-Auteur.rice PANDC; 5-Autrice; Pakistan (corpus analysé); _Nettoyé

Brown Girls Who don’t Need Saving: Social Media and the Role of ‘Possessive Investment’ in The Mindy Project and The Good Wife - Moorti, Sujata (Television for Women, 2016)
This poignant assertionby acclaimed actor Viola Davis, star of the series How to GetAway with Murder (ABC, 2014-), during her Emmy acceptance speechwent viral and becamethe flashpoint for heated discussion about contemporary television’s representational practices. The statement draws attention to questions of taste, what is acknowledgedby the industry and audiences as quality television and the political economy of thecontemporary industry. This moment in television history, with its attendant socialmedia afterlife, captures the key elements I wish to explore in this chapter: represen-tations of women of colour, production practices and viewer responses. As Viola Davisnotes in the quote above, the contemporary US television landscape offers limited rolesfor people of colour. The few shows starring people of colour have become the focus ofintense social media exchanges. In this chapter, I will explore how televisual womenof colour have become a key site from which viewers assert a possessive investmentof racialised identity. By focusing on social media responses, I delineate the ways inwhich viewers invest symbolic and literal ownership over these representations.Through such a multifaceted examination, this essay aims to elaborate how women ofcolour are accommodated within the concept of television for women, a term inter-rogated in this volume. In addition, I illustrate the ideological instability of the term‘women of colour’ and the capaciousness of the concept ‘television for women’.
Num Pages: 20
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Shaded Lives: African-American Women and Television - Smith-Shomade, Beretta E. (Rutgers University Press, 2002)
Since its invention, television has been one of the biggest influences on American culture. Through this medium, multiple visions and disparate voices have attempted to stake a place in viewer consumption. Yet even as this programming supposedly reflects characteristics of the general American populace, television-generated images are manipulated and contradictory, predicated by the various economic, political, and cultural forces placed upon it. In Shaded Lives, Beretta Smith-Shomade sets out to dissect images of the African American woman in television from the 1980s. She calls their depiction "binaristic," or split. African American women, although an essential part of television programming today, are still presented as distorted and deviant. By closely examining the television texts of African-American women in comedy, music video, television news and talk shows (Oprah Winfrey is highlighted), Smith-Shomade shows how these voices are represented, what forces may be at work in influencing these images, and what alternate ways of viewing might be available. Smith-Shomade offers critical examples of where the sexist and racist legacy of this country collide with the cultural strength of Black women in visual and real-lived culture. As the nation's climate of heightened racial divisiveness continues to relegate the representation of Black women to depravity and display, her study is not only useful, it is critical.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Romance in Post-Socialist Chinese Television - Wen, Huike (Palgrave Macmillan, 2020)
"Surveying the latest Chinese TV shows centered on romantic relationships, this book joins the expanding body of literature on the ever-evolving structures of feelings while breaking new grounds in media studies. With its thorough investigation of a wide range of genres, narratives, and public discourses, the volume makes timely and significant contributions to the fields of media studies, China studies, and the cultural history of love and romance."–Hui Faye Xiao, University of Kansas, USA "What does romantic love mean for Chinese people today? How is love represented in popular Chinese television programs? Huike Wens fascinating and important book explores how romantic love promises young Chinese urbanites individual freedom, fulfillment, and purpose in life, yet also plays an ideological role in creating social cohesion and maintaining traditional patriarchal values in post-socialist China. An entertaining and thought-provoking insight into how love functions in contemporary Chinese society." –Hsu-Ming Teo, Macquarie University, Australia This book examines how representations of romantic love in Chinese television programs reflect the contradictions inherent to changing dominant values in post-socialist Chinese mainstream culture. These representations celebrate individual freedom, passion, and gender equality, and promise change based on individual diligence and talent, while simultaneously obstructing the fulfillment of these ideals. Huike Wen is an Associate Professor at Willamette University (Salem, Oregon). Her research focuses on the intersection of genders, emotions, media technology, and nations in transnational Chinese and East Asian media and culture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Television and the Modernization Ideal in 1980s China: Dazzling the Eyes - Wen, Huike (Lexington Books, 2013)
Television and the Modernization Ideal in 1980s China: Dazzling the Eyes explores Chinese television history in the pivotal decade of the 1980s and explains the intellectual reception of television in China during this time. While the Chinese media has often been a topic within studies of globalization and the global political economy, scholarly attention to the history of Chinese television requires a more extensive and critical view of the interaction between television and culture. Using theories of media technology, globalization, and gender studies supplemented by Chinese periodicals including Life Out of 8 Hours, Popular TV, Popular Cinema, Modern Family, and Chinese Advertising, as well as oral history interviews, this book re-examines how Western technology was introduced to and embedded into Chinese culture. Wen compares and analyzes television dramas produced in China and imported from other nations while examining the interaction between various ideologies of Chinese society and those of the international media. Moreover, she explores how the hybridity between Western television culture and Chinese traditions were represented in popular Chinese visual media, specifically the confusions and ambitions of modernization and the negotiation between tradition and modernity, nationalism and internationalism, in the intellectual reception of television in China.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Real Housewives or Real Lies? New Constructions of "Housewives" on The Real Housewives of Atlanta - Shorter, Shavonne R. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
An old adage prescribed that “art imitates life.” If one believes this to be true, then it is plausible that entertainment is a source from which information about everyday life can be gleaned? Can U.S. television shows provide a looking glass into how Americans perform certain aspects of their lives? For a “real” look into how careers are performed, I have examined content from a reality television show which bears a title that implies something about the cast— the Bravo Network’s Real Housewives of Atlanta series. This show was chosen for two reasons. First, The Real Housewives of Atlanta is the most popular show among the “Housewives” franchise. Thus with each airing of the show, those who watch have the opportunity to learn more about the career aspirations, roles, and behaviors, of the cast members. Second, this is the only show within The Real Housewives franchise that features a primarily black cast. As such, the question emerges— can this show provide insight into the way black women construct their career roles? Another goal of this study is to determine how cast members construct notions of housewifery. Hence, throughout this chapter, readers will see that these women are not the typical “housewives,” rather they have reinvented what it means to be a housewife in the modern age.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

The "Down Ass Bitch" in the Reality Television Show Love and Hip Hop: The Image of the Enduring Black Women and Her Unwavering Support of the Black Man - Alameen-Shavers, Antwanisha (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Within Spoken Soul, better known as Ebonics, the term down can be used as an adjective to describe a person that willingly yields a tremendous amount of support to another person. The “Down Ass Bitch” (DAB) is a controlling image of the black woman that calls for her unwavering support of the black man, even when it is pernicious to her best interest. In fact, we can see this in the black community on many levels: (1) from black women faithfully waiting years for men to be released from prison; (2) hiding domestic abuse or rape at the hands of black men for the sake of protecting the race; or (3) sexually exploiting our bodies for the financial benefit of black men. However, what is most interesting about this particular stereotype of the black woman being “down” for her man is that this is not an expectation that is asked of the black man. It is this author’s contention that the “Down Ass Bitch” is obsequious to the powers of black men— though she is portrayed as being strong, aggressive, and assertive. Essentially, the “Down Ass Bitch,” a highly celebrated image in the black community, is the black version of the submissive white woman, the Eurocentric construction of the idealized womanhood. Various controlling images of black womanhood— such as the mammy, the jezebel, and the welfare queen— served as justifications for the oppression of black women and have been discussed significantly by scholars.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Dehumanized and Empowered? Black Women, Reality Television, and Love and Hip Hop Atlanta - Bennett, Patrick; Griffin, Rachel Alicia (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
In recent years, scripted television has been joined by a more “realistic” look into peoples’ lives— reality television. Reality television claims to give viewers an unmediated glimpse into how real people live. The “realness” of reality television invokes controversy by providing a voyeuristic and potentially exploitive look into people’s lives. As the genre has matured, shows that offer insight into communities that are systemically underrepresented have become common. Indicative of this trend are shows that depict the lives of African Americans and opportunistically exploit representations of black culture for drama, ratings, and profit. One network that has taken considerable advantage of this is VH1— first, with the success of Flavor of Love and its spinoffs, then more recently with shows such as Basketball Wives and Love and Hip Hop. In fact, the excessive amount of fighting among Black women on Basketball Wives led to a boycott of the show, which prompted creator Shaunie O’Neal to promise less violence in its next season. Akin to Basketball Wives , Love and Hip Hop Atlanta exemplifies the trend of exploiting black culture. As members of the black community, we find ourselves both intrigued and troubled by the implications of the show. Capturing the essence of our paradoxical interpretation of Love and Hip Hop Atlanta — as one of many reality television shows that simultaneously reproduces and challenges negative stereotypes about blackness— are contradictory headlines such as “The 21 Most Ratchet Women of Black Reality TV,” “How Reality TV has Changed our Daughters,” and “Wealthy Reality Stars Humanize Black Women.”
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

A Critical Analysis of Black Womahood in NBC's The Apprentice - Griffin Padget, Donyale R.; Allison, Donnetrice C. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Reality programs rose to prominence based on claims that the shows depicted “real life,” but in recent years many shows have come under fire for being anything but “reality.” Orbe (1998) suggests viewers are drawn to such programs based on the notion that they show “real people in everyday interactions,” and there is a certain level of “unpredictability that comes with reality.” However, what has become predictable and potentially problematic, over the past two decades, are the negative stereotypes associated with African American women on these programs. This skewing of reality is particularly significant when we consider the limited opportunities these shows provide viewers to witness the many facets of black womanhood. From the head-bobbing and finger-waving of Alicia Calaway on season two of the hit show Survivor to the on-and-off-air mudslinging between Kenya Moore and NeNe Leakes of Real Housewives of Atlanta fame, black women are portrayed as disloyal, bitchy, lazy, difficult to work with, and a threat to others.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

The "Tyra Tyrade": Reinforcing the Sapphire Through Online Parody - Patton, Tracey Owens; Snyder-Yuly, Julie (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Tyra Banks, supermodel and producer, is the creator of the reality show America’s Next Top Model ( ANTM ), which is now in its twenty-second cycle, and features contestants who present themselves to a panel of judges for modeling critique. ANTM has been nominated for twenty-nine awards, including the GLAAD Media Award and Image Award, and the show has received five awards in 2009 from the Teen Choice Award and the Director’s Guild of America Award. Further, ANTM is currently shown in over 120 countries. The winner of each cycle receives a featured spread in a magazine, a modeling contract with a prominent agency, and a $100,000 modeling contract from a cosmetics company. In 2005, however, there was an infamous episode— dubbed the “Tyra Tyrade,” —where Tyra Banks yelled at a contestant whom she had just eliminated from the show. This episode was parodied more than any other ANTM episode, with the penultimate parody shown on a 2007 episode of Family Guy (a primetime cartoon television show with millions of viewers each week), where Tyra turns into a lizard and eats the model. While this episode is now nine years old, parodies from as recently as 2014 continue to live on and, as we argue, perpetuate negative stereotypes of black womanhood, particularly as related to the Sapphire mediated stereotype— loud, bossy, angry black woman. From the various interpretations of the “Tyra Tyrade,” it is clear that those who created the parodies covertly and overtly ventured into maintaining white supremacist stereotypes of black womanhood— where one is supposed to be beautiful, a jezebel, or a mammy, but not a Sapphire. Continuing the marginalizing mediated tradition, in almost every parody, the Tyra character becomes the object of ridicule for being “excessively black” and outside the parameters of her hegemonically prescribed role, because she demonstrated negative emotions resulting in an assertion of her power as the expert.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Is She Strong or Just a B!@*#? Discussion of Black Women's Anger in the Reality Show Bad Girls Club - Goldman, Adria Y. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
It is near impossible to have a discussion of black women in reality television without mentioning the infamous Angry Black Woman (ABW). In fact, some critiques have argued reality television is damaging for black women since many shows focus heavily on this character. 1 This stereotypical characterization of black women is long-standing, due largely to its constant inclusion in media messages. As noted in chapter one, audiences were first officially introduced to her in the 1920s as Sapphire Stevens from the Amos ‘n’ Andy Show ; and her character continued to resurface throughout the years, across several different genres. Despite the many time periods through which this image has traveled, the key characteristic of the Sapphire— her unexplainable anger and aggression— seem to resonate in many modern day images of black women.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Can't Have It All: An Analysis of Black Motherhood on Reality Television - Alford, Allison M.; Maxwell, Madeline M.; Jones, Ryessia D.; Morris, Angelica N. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
In this chapter we analyze three reality TV (RTV) shows whose main characters do not fit the old movie stereotypes of dark-skinned maternal Mammies, bossy, brown Sapphires or light-skinned sexy Jezebels. Many RTV shows with black cast members are falling back on such stereotypical representations. In contrast, the female characters we analyze are smart and sophisticated, and they live in multi-racial environments. Hence, the primary mediarelated question we address concerns how one slice of black motherhood is represented. The social question we address concerns the extent to which the character presentations actually point to social progress, with diverse symbols and meaning making of real life, or are they as artificial and stereotypical— perhaps in new ways— as the old portrayals?
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Are Black Women Loud? Neoliberal and Postfeminist Protagonists in OWN's Televisual Sphere - Briceño, Mia E.; Estwick, Evene (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Jones’ comments reflect a general consensus among TV critics and viewers that: 1) the black women who command the most attention on reality television tend to portray stereotypical, Sapphire-like characters; 2) as audiences consume such portrayals, there is a consistent line of argument from producers that insists “pitting [black women] against each other” is expected or “what the people want;” and 3) black female reality TV stars are willing to indulge the Sapphire fantasy if it means they will be able to further a personal and/or professional agenda. These are important themes to interrogate, especially given the history of mass mediated representations of black Americans, as well as the present-day “evolution” of black characters and other characters of color on unscripted and scripted American television. However, because attention is primarily focused on arguably “negative” portrayals, there has not been much critical analysis of “alternative” or more nuanced portrayals of black women in the televisual sphere. This chapter represents an attempt to fill in some of that blank space by focusing attention on an underexplored and relatively new consortium of reality television programming that features black women who are defined by their roles as mothers and entrepreneurs.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

From 1990s Girl to Hip-Hop Wife: An Analysis of the Portrayal of Tiny as Black Mother in Reality Television - Jones, Ryessia D.; Jones, Johnny; Smith, Siobhan E. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Although African-American women are still underrepresented in narrative television, reality television appears to be a site where one can find many portrayals of them. As other scholars have explained, the representations of African American women in reality television are usually negative, generally presenting them as loud, angry, and without “class.” However, there has been little research on the complicated relationships of black motherhood, black wifehood, and their portrayals on reality television. One black mother who illustrates this tense interaction is Tameka “Tiny” Harris, nee Cottle, formerly of the 1990s girl group Xscape, and star of two reality television programs— BET’s Tiny & Toya , and VH1’s T.I. and Tiny: The Family Hustle . Though both programs prominently feature Cottle, BET’s program constructs Tiny as an emotionally strong and pragmatically capable business woman who maintains the emotional health and financial stability of her family while her relational partner/husband, rapper Tip “T.I.” Harris, is serving time in prison. However, upon T.I.’s return home, The Family Hustle presents Tiny as having little business savvy and as overly permissive with their blended family. This is a dangerous portrayal, given that reality TV purports to disseminate some version of “reality” to its viewers.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Queering/Quaring Blackness in Noah’s Arc - Yep, Gust A.; Elia, John P. (Queer Popular Culture: Literature, Media, Film, and Television, 2007)
This chapter provides a description and critical analysis of Noah’s Arc , a Logo cable television series featuring a predominantly African American gay male cast. Queer theory and quare studies are used as theoretical tools to examine the conceptions of blackness in general, as well as representations of blackness in Noah’s Arc . Thereafter this chapter turns to an analysis of the representations in this series to illustrate how Noah’s Arc not only queers and quares notions of authentic blackness but also serves to expand various notions of blackness. Finally, this chapter provides a treatment of how whiteness and heteronormativity are implicated in this recent iteration of a racialized queer visibility in popular culture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

The Paramilitary Hero on Turkish Television: A Case Study on Valley of the Wolves - Çetin, Berfin Emre (Cambridge Scholars Publisher, 2015)
The Paramilitary Hero on Turkish Television: A Case Study on Valley of the Wolves explores the representation and reception of nationalism and masculinity in Turkey through an examination of the popular television serial, Valley of the Wolves which has been aired on Turkish television since 2003. This detailed examination of the show demonstrates a particular discourse of nationalism, namely the Turkish Islam synthesis embedded in a gender-specific regime in which the paramilitary hero is placed at the centre. The study draws on thirty-seven in-depth interviews with viewers of the programme from different social backgrounds. These viewers read the serial from various perspectives in the light of their gendered experiences, suggesting that the relationship between text and audience is not necessarily predetermined by the former, but is rather constructed through an interdiscursive process. The book also examines the pleasures of the “contesting” readers of Valley of the Wolves, drawing on the audience interviews, and argues that critical approaches to a particular media text do not present a barrier to audience pleasures.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Women, Television and Everyday Life in Korea: Journeys of Hope - Kim, Youna (Taylor & Francis Group, 2006)
Fusing audience research and ethnography, the book presents a compelling account of women's changing lives and identities in relation to the impact of the most popular media culture in everyday life: television. Within the historically-specific social conditions of Korean modernity, Youna Kim analyzes how Korean women of varying age and class group cope with the new environment of changing economical structure and social relations. The book argues that television is an important resource for women, stimulating them to research their own lives and identities. Youna Kim reveals Korean women as creative, energetic and critical audiences in their responses to evolving modernity and the impact of the West. Based on original empirical research, the book explores the hopes, aspirations, frustrations and dilemmas of Korean women as they try to cope with life beyond traditional grounds. Going beyond the traditional Anglo-American view of media and culture, this text will appeal to students and scholars of both Korean area studies and media and communications studies.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Corée du Sud (corpus analysé); France (lieu de production du savoir); _Nettoyé

Graphic Blackness/Anime Noir: Aaron McGruder’s the Boondocks and the Adult Swim - Whaley, Deborah Elizabeth (Watching While Black, 2012)
Aaron McGruder’s “The Return of the King” (2006) is one of many of the artist’s controversial episodes, yet it stands out because of the criticism it received among mainstream media outlets and civil rights leaders. It was the ninth episode to air from his series The Boondocks, which is an anime show that airs on the Cartoon Network’s Adult Swim cable channel. McGruder presents the following scenario in “The Return of the King”: What if Martin Luther King Jr. (MLK) did not die after his April 4, 1968, shooting and instead awoke after being in a coma for thirty-two years?
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Nigger, Coon, Boy, Punk, Homo, Faggot, Black Man: Reconsidering Established Interpretations of Masculinity, Race, ans Sexuality Through Noah’s Arc - Cunningham, Mark D. (Watching While Black, 2012)
At best, our knowledge about the lives and experiences of Black gay men is limited to a series of stereotypes, snap judgments, and ridicule. In terms of television media product, this aforementioned knowledge has been packaged mostly within the framework of comedy: a red-leather-clad Eddie Murphy talking about the most effective ways to shield his ass from the gay male gaze in the 1983 HBO stand-up performance Delirious ; Damon Wayans and David Alan Grier’s effeminate film critics Blaine Edwards and Antoine Merriweather on the 1990s television variety show In Living Color ; fashionista panel members Miss J and Andre Leon Talley
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Prioritized: The Hip Hop (Re)Construction of Black Womanhood in Girlfriends and the Game - Lewis, Nghana (Watching While Black, 2012)
Why is it important that a Black woman created, wrote for, and co-produced¹ two highly-regarded television situation comedies that engaged a variety of Black women’s health issues while at the same time these issues were being reduced, simplified, or altogether ignored in mainstream American hip hop? Mara Brock Akil tacitly responded to this question when asked why four episodes of the third season of Girlfriends (2000–2008), the situation comedy she created and co-produced for UPN, addressed the HIV/AIDS crisis among Black women in America. “I have things I want to say,” explained Brock Akil, “about bridging television’s gap between
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Consuming Halal Turkish Television in Indonesia: A Closer Look at the Social Responses Towards Muhteşem Yüzyıl - Rakhmani, Inaya; Zakiah, Adinda (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter unpacks the tension between secular, modern values and conservative, Islamic interpretations within the Indonesian middle class by taking the consumption of Turkish popular cultural products as a case. The chapter explicates the social responses towards the first Turkish television drama aired on terrestrial, private television in Indonesia: The Magnificent Century (Muhtesṃem Yüzyıl/Abad Kejayaan). This chapter understands the reproduction of secular and conservative Islamic values, while in contestation, as a response to broader global, market-capitalist developments. It finds that in response to audience criticism regarding the “un-Islamic” portrayal of the epoch in the drama—specifically the depiction of women as concubines—television stations enlisted the services of Muslim clerics to correct or justify the representation of historical facts. This reveals that market-driven self-censorship has opened up ways for Muslim clerics to influence television content. As such, the chapter argues that market-capitalist forces discursively use Islamic authority as a way to legitimise the halal consumption of Turkish drama among Indonesian Muslim audience at the expense of programme diversity.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Indonésie (corpus analysé); Indonésie (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé

Refashioning Chinese Television Through Digital Fun - Bai, Ruoyun (The Routledge Companion to Global Television, 2019)
This chapter discusses how Chinese television has been refashioned by the digital entertainment industry, and contends that new genres, identities, and representations have emerged in recognition of youths as the most valuable and desirable category of audience. It does so by way of three case studies. The first illustrates the symbiotic relationship between online literature and television drama production, and how the former contributes to the fantastical turn of Chinese television. The second seeks to understand the emergence of new cultural figures of “supreme heroine” and “sweet males” in the context of the rise of female fandom in contemporary Chinese popular culture. The third reveals how traditional television content, or in this case a political drama, may be recreated by online distributors and influencers so as to be aligned with the habits, attitudes, and preferences of the younger audiences. The chapter concludes that to understand contemporary Chinese television culture, the Internet and social media must become an integral component of inquiry because of their powerful remediating role in the public communication of any cultural text.
Num Pages: 12
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Identités diasporiques; Canada (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

The Social and Political Dimensions of Global Television Formats: Reality Television in Lebanon and Saudi Arabia - Kraidy, Marwan (Global Television Formats: Understanding Television Across Borders, 2012)
When scholars and policy makers contemplate the Arab “media revolution,” they mostly think of Al-Jazeera and its news competitors. They are guided by the assumption that all-news satellite television networks are the predominant, even the single, shaper of the Arab public sphere, a perspective exacerbated by the September 11, 2001 attacks. Drawing on a larger work (Kraidy, 2009, forthcoming), this chapter presents an alternative view, emphasizing instead the combined impact of Arab entertainment television and small media such as mobile phones on Arab governance. It explores how entertainment television is an active contributor to shaping what Arab publics discuss and do in both the social and political realms. As local (in this case regional/pan-Arab, reaching two dozen Arabic-speaking countries) adaptations of global television formats, Arab reality television shows exhibit a combination of signs and practices from several worldviews. As such, this chapter will show how Arab reality shows are open to multiple processes of appropriation and redeployment. Though numerous scholars have for years studied the differentiated “reception” of television texts in various contexts, this chapter focuses speciﬁcally on television formats in a context of growing media convergence and protracted political instability and social upheaval. Speciﬁcally, it focuses on reality television’s social and political impact, which stems primarily from its activation of new communication processes between a variety of information and media technologies creating what I call “hypermedia space.” In the new Arab information order, reality television activates hypermedia space because it promotes participatory practices like voting, campaigning and alliance building, via mobile telephones and related devices.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Arabie Saoudite (corpus analysé); Liban (corpus analysé); Qatar (lieu de production du savoir); _Nettoyé